The involvement of T lymphocytes in the pathogenesis of endometriotic tissues overgrowth in women with endometriosis - Krzysztof Szyllo; Henryk Tchorzewski; Malgorzata Banasik; Ewa Glowacka; Przemyslaw Lewkowicz; Anna Kamer-bartosinska (Hindawi Limited, 2003)
Background: Endometriosis, uncontrolled proliferation of ectopic and eutopic endometriotic tissues, is common in women at reproductive age, and may affect fertility. The role of macrophages in the pathogenesis is well proved, but engagement of T cells in the pathogenesis of endometriosis is a matter of controversy